Final draft PAME Work Plan for the SAO Report to Ministers. - Protection of the Arctic Marine Environment (PAME) (Protection of the Arctic Marine Environment (PAME), 2015)
Work plan draft as of 2015-02-17 for the years 2015-2017, submitted by the Arctic Council working group Protection of the Arctic Marine Environment (PAME) to the Arctic Council's Senior Arctic Officials meeting in Whitehorse, Canada, March 4-5 2015. NOTE: Attachments include the work plan draft, as well as the cover letter.